If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 2x + -9 Reorder the terms: 1 + 5x = 2x + -9 Reorder the terms: 1 + 5x = -9 + 2x Solving 1 + 5x = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 5x + -2x = -9 + 2x + -2x Combine like terms: 5x + -2x = 3x 1 + 3x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 3x = -9 + 0 1 + 3x = -9 Add '-1' to each side of the equation. 1 + -1 + 3x = -9 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = -9 + -1 3x = -9 + -1 Combine like terms: -9 + -1 = -10 3x = -10 Divide each side by '3'. x = -3.333333333 Simplifying x = -3.333333333
| 3cos^2x=3-cos^2x | | 4x+1=15+2x | | 4y^2+34y=-144 | | -6x-28+8x=14 | | 20-2P=-10+4P | | [8+5y]=14 | | 3.5x+-20+.5x=40-2x | | -7=6-C | | 7x+5x-65=79 | | 9y=5x-7 | | 5x+8y+4xy= | | Y=24x+15 | | 4x+2=-25 | | 27-9x+15y=0 | | 4cosx+2=cosx+1 | | 6-9p-2= | | 3ln(x-2)+6=7 | | y+2-3y=-18 | | 5x+8=5(x+2) | | 10x-35=3x-7 | | 8x-16=7x+4 | | 2(4x-5)=17 | | 50x-2y=50 | | -86+11x-2x=121 | | 3p+8+2p=28 | | 9x+6x-91=104 | | 4(2x+1)+3(2x+1)= | | 2x^4-9x^2+9=0 | | 4a+1-a=8 | | (5+3x)(7-x)=0 | | 7x^2-18x+108=0 | | 6x+5=-x+19 |